(untitled) (Journal of Mathematical Study, 2018)
In this note, for k-quasiconformal mappings of a bounded domain into the complex plane, we give an upper bound of Burkholder integral. Moreover, as an application we obtain an upper bound of the L^p-integral of J_f and |Df| for certain K-quasiconformal mappings.